Pathogenicity and identification of host adaptation genes of the avian pathogenic Escherichia coli O145 in duck - Tan, Mei-Fang; Tan, Jia; Fang, Shao-Pei; Kang, Zhao-Feng; Li, Hai-Qin; Zhang, Fan-Fan; Wu, Cheng-Cheng; Li, Na; Zeng, Yan-Bin; Lin, Cui (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionAvian pathogenic Escherichia coli (APEC) is a critical bacterial pathogen that causes severe infections in poultry. Diverse serotypes increase the complexity of treatment and controlling APEC infections. Recent epidemiological investigations indicate O145 is emerging as a predominant serogroup of APEC in China. However, limited information is known about this newly emerged serogroup.MethodsA virulent strain, NC22, was selected to elucidate the mechanisms underlying APEC O145-related pathogenicity and host adaptation. Whole-genome sequencing and pathogenicity assays was conducted on this strain. We further performed a transcriptional analysis of the bacteria during the early colonization stage in the duck liver and compared them with those in liquid cultures in vitro.ResultsSubcutaneous inoculation of NC22 induced typical symptoms in ducks. The bacterial loads in the blood and various tissues peaked at 2 and 3 days post infection, respectively. The affected tissues included the heart, liver, spleen, lung, kidney, bursa of Fabricius, duodenum, jejunum, and cecum. We then analyzed the transcriptome profiles of NC22 during growth in duck liver versus lysogeny broth and identified 87 genes with differential expression levels.These included key metabolic enzymes and recognized host adaptation factors. Analysis of the metabolic pathways revealed an inhibition of the metabolic shift from glycolysis towards pentose phosphate pathway and an interference of the citrate cycle. Moreover, significantly differentially expressed small regulatory RNAs were examined, such as SroC, CsrC, and GadY.DiscussionThese findings enhance our understanding of the pathogenicity of APEC O145 and the molecular mechanisms underlying APEC-related pathogen−host interactions.